2015
DOI: 10.1080/15022250.2015.1006391
|View full text |Cite
|
Sign up to set email alerts
|

People, Places, Protected Areas and Tourism: Place Attachment in Rossport, Ontario, Canada

Abstract: Place attachment is spatially and temporally anchored in the local context, affecting how residents perceive proposed development strategies. As such, we examine, through the analysis of 18 interviews conducted with residents from Rossport, Ontario, Canada, how place attachment and historical antecedents (or lack thereof) have influenced the acceptance of, or opposition to, conservation and tourism strategies in and near the village of Rossport, Ontario. The analysis of the interviews suggests that some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…This is reflected in a study by Raadik Cottrell and Cottrell (2015) who found that sense of place influences perceived environmental change and the effects on future holiday experiences to Saaremaa in Estonia. Sense of place can also help better understand the acceptance of, or opposition to, conservation and tourism strategies among local populations (Lemelin et al, 2015). Learning and interpretation are other themes recognized, related to the role of guides as well as tourists' nature connections.…”
Section: Current State Of Nature-based Tourism Research -A Nordic Outmentioning
confidence: 99%
“…This is reflected in a study by Raadik Cottrell and Cottrell (2015) who found that sense of place influences perceived environmental change and the effects on future holiday experiences to Saaremaa in Estonia. Sense of place can also help better understand the acceptance of, or opposition to, conservation and tourism strategies among local populations (Lemelin et al, 2015). Learning and interpretation are other themes recognized, related to the role of guides as well as tourists' nature connections.…”
Section: Current State Of Nature-based Tourism Research -A Nordic Outmentioning
confidence: 99%
“…As relações possíveis de observação entre meio físico e biótico e entre os próprios organismos de diferentes ordens, propiciam a reflexão sobre o ser humano como parte da dinâmica da natureza. Lemelin et al (2015) indicam que um dos aspectos do ceticismo da população local, próxima às áreas protegidas, relacionados a iniciativas de desenvolvimento do turismo associado à conservação, deriva do desconhecimento do processo histórico de produção do espaço, que dificulta o desenvolvimento do sentido de pertencimento a uma comunidade, a um território ou ao que Zaoual (2006) chamava de sítio simbólico de pertencimento.…”
Section: Cenário: Uso Público Em áReas Protegidasunclassified
“…Other scholars scrutinizing place attachment have applied similar approaches, likewise using various interviewing methods and smaller samples (e.g. Åkerlund & Sandberg, 2015;Gustafson, 2001;Lemelin, Koster, Bradford, Strickert, & Molinsky, 2015;Tuulentie & Heimtun, 2014;Ujang & Zakariya, 2015;Windsong, 2014). The present study similarly draws upon semi-structured interviews, here addressing tourism actors in the Jukkasjärvi (Kiruna) area.…”
Section: Case Study and Methodological Approachmentioning
confidence: 99%